2006
DOI: 10.1161/01.res.0000225284.36490.a2
|View full text |Cite
|
Sign up to set email alerts
|

A Sphingosine-1–Phosphate-Activated Calcium Channel Controlling Vascular Smooth Muscle Cell Motility

Abstract: Abstract-In a screen of potential lipid regulators of transient receptor potential (TRP) channels, we identified sphingosine-1-phosphate (S1P) as an activator of TRPC5. We explored the relevance to vascular biology because S1P is a key cardiovascular signaling molecule. TRPC5 is expressed in smooth muscle cells of human vein along with TRPC1, which forms a complex with TRPC5. Importantly, S1P also activates the TRPC5-TRPC1 heteromultimeric channel. Because TRPC channels are linked to neuronal growth cone exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
173
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(183 citation statements)
references
References 49 publications
10
173
0
Order By: Relevance
“…9. Furthermore, in smooth muscle cells, S1P-induced migration is dependent on activation of TRPC5 (40). In light of our observation and the significance of S1P in enhancing the migration of several cancer cells, it would thus be of interest to more closely investigate the relationships between S1P and TRPC-dependent calcium entry also in other cancer cells.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…9. Furthermore, in smooth muscle cells, S1P-induced migration is dependent on activation of TRPC5 (40). In light of our observation and the significance of S1P in enhancing the migration of several cancer cells, it would thus be of interest to more closely investigate the relationships between S1P and TRPC-dependent calcium entry also in other cancer cells.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, S1P enhanced calcium entry through stretch-activated TRPC1 channels in skeletal muscle cells (39). In vascular smooth muscles cells, S1P activates TRPC5 via a receptor-mediated mechanism (40).…”
Section: Discussionmentioning
confidence: 99%
“…Receptors coupled to G␣ i2 primarily activate TRPC4 and receptors coupled to G␣ i3 primarily activate TRPC5 to mediate the receptor-stimulated monovalent cation current and the Ca 2ϩ influx. Several studies have reported modulation of TRPC4 and TRPC5 activity by GTP␥S-activated PTX-sensitive G-proteins and G i/o -coupled receptors (6,8,25). Activation of TRPC4 by muscarinic receptor stimulation of GI smooth muscle was inhibited by PTX and was shown to be critical in evoking and regulating GI tract motility (21).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also suggested that PTX-sensitive G-proteins play an important role in the activation process of TRPC4 and TRPC5 by GPCR (6,8,25). In our previous study, we showed that G␣ i2 activates TRPC4␤ and that PTX inhibits the activation of TRPC4␤ by stimulation of M2 muscarinic receptors (25).…”
Section: Transient Receptor Potential Canonical (Trpc)mentioning
confidence: 99%
“…TRPC3 has been shown to be involved in the agonist-induced depolarization and vasoconstriction of arterial SMCs, and suppression of TRPC3 expression was found to significantly decrease the depolarization and constriction of intact cerebral arteries in response to UTP [37]. Xu et al [38] found that sphingolipids and TRP channels are functionally linked in VSMCs and that the sphingolipids' metabolite, sphingosine-1-phosphate, activates TRPC5, thus controlling VSMC motility. TRPC6 has been suggested to have a major role in the regulation of myogenic tone [39].…”
Section: Trp Channels Participate In Vasoconstrictionmentioning
confidence: 99%